REM Sleep EEG Instability in REM Sleep Behavior Disorder and Clonazepam Effects. Issue 8 (6th May 2017) - Ferri, Raffaele; Rundo, Francesco; Silvani, Alessandro; Zucconi, Marco; Bruni, Oliviero; Ferini-Strambi, Luigi; Plazzi, Giuseppe; Manconi, Mauro
Abstract: Study Objectives: We aimed to analyze quantitatively rapid eye movement (REM) sleep electroencephalogram (EEG) in controls, drug-naïve idiopathic REM sleep behavior disorder patients (iRBD), and iRBD patients treated with clonazepam. Methods: Twenty-nine drug-naïve iRBD patients (mean age 68.2 years), 14 iRBD patients under chronic clonazepam therapy (mean age 66.3 years), and 21 controls (mean age 66.8 years) were recruited. Power spectra were obtained from sleep EEG (central derivation), using a 2-second sliding window, with 1-second steps. The power values of each REM sleep EEG spectral band (one every second) were normalized with respect to the average power value obtained during sleep stage 2 in the same individual. Results: In drug-naïve patients, the normalized power values showed a less pronounced REM-related decrease of power in all bands with frequency <15 Hz than controls and an increase in the beta band, negatively correlated with muscle atonia; in patients treated with clonazepam there was a partial return of all bands <15 Hz toward the control values. The standard deviation values of the normalized power were higher for untreated patients in all EEG bands and were almost completely normalized in patients treated with clonazepam. Conclusions: The REM sleep EEG structure changes found in this study disclose subtle but significant alterations in the cortical electrophysiology of RBD that might represent the early expression of the supposed neurodegenerative processes already taking place at this stage of the disease and might be the target of better and effective future therapeutic strategies for this condition.